2011
DOI: 10.1094/pdis-09-10-0670
|View full text |Cite
|
Sign up to set email alerts
|

Management of Verticillium Wilt of Potato with Disease-Suppressive Green Manures and as Affected by Previous Cropping History

Abstract: Larkin, R. P., Honeycutt, C. W., and Olanya, O. M. 2011. Management of Verticillium wilt of potato with disease-suppressive green manures and as affected by previous cropping history. Plant Dis. 95:568-576.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Sharp eyespot usually occurs more often in continuously cropped cereals, including particularly wheat (Colbach et al 1997;Żółtańska 2005). White mustard used at Mochełek as the pre-preceding crop seemed not to contribute to disease suppression, although volatiles released from breakdown of thioglycosides have shown activity against soil-borne pathogens (Larkin et al 2011). Low nitrogen rates at Mochełek did not decrease disease incidence as reported by Colbach et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…Sharp eyespot usually occurs more often in continuously cropped cereals, including particularly wheat (Colbach et al 1997;Żółtańska 2005). White mustard used at Mochełek as the pre-preceding crop seemed not to contribute to disease suppression, although volatiles released from breakdown of thioglycosides have shown activity against soil-borne pathogens (Larkin et al 2011). Low nitrogen rates at Mochełek did not decrease disease incidence as reported by Colbach et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…The lower incidence and severity of disease at Dębina, Kończewice, and Minikowo may have resulted from the use of winter oilseed rape as the preceding crop. Volatiles released from the breakdown of thioglycosides produced by oilseed rape have shown antagonistic activity towards soil-borne pathogens (Larkin et al 2011). Yellow and narrow-leaved lupins, used as the preceding crop at Chrząstowo, do not produce compounds that could inhibit the growth and activity of Rhizoctonia.…”
Section: Discussionmentioning
confidence: 99%
“…Certain plants have been shown to produce chemicals that act as biofumigants, controlling or reducing harmful soil fungi, similar to those that may cause charcoal rot. Bacterial control of diseases has been used successfully in potato (Larkin et al, 2011) and cacao production (Melnick et al, 2008). Mengistu et al (2009) showed some suppression of charcoal rot infestation with altered tillage and use of rye as a cover crop.…”
Section: Introductionmentioning
confidence: 99%